2018
DOI: 10.1080/19440049.2018.1463569
|View full text |Cite
|
Sign up to set email alerts
|

LC-MS/MS-based determination of chloramphenicol, thiamphenicol, florfenicol and florfenicol amine in poultry meat from the Punjab-Pakistan

Abstract: A simple, reliable and sensitive liquid chromatography-tandem mass spectrometry-based confirmatory method was redeveloped and validated for the simultaneous determination of chloramphenicol, thiamphenicol, florfenicol and florfenicol amine in chicken muscles. The analytes were extracted from minced chicken muscle with acetonitrile and ammoniated water mixture. A second extraction with ethyl acetate was followed by evaporation and dissolution of the residue in ammoniated methanol before defatting with n-hexane.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Different mobile phase compositions were used for the best separation of CAP, TAP, FF, and FFA on a C 18 column. FFA is a highly polar drug metabolite and is poorly retained on C 18 columns under neutral mobile phase conditions . Barreto et al reported that the addition of 2mM ammonium acetate to the mobile phase allowed good separation of CAP, TAP, FF, and FFA and favoured FFA retention on C 18 columns under alkaline conditions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Different mobile phase compositions were used for the best separation of CAP, TAP, FF, and FFA on a C 18 column. FFA is a highly polar drug metabolite and is poorly retained on C 18 columns under neutral mobile phase conditions . Barreto et al reported that the addition of 2mM ammonium acetate to the mobile phase allowed good separation of CAP, TAP, FF, and FFA and favoured FFA retention on C 18 columns under alkaline conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Various extraction methods were employed to extract CAP, TAP, FF, and FFA from animal-derived foods. These methods included LLE, 10,12,17,19,20 fabric-phase sorptive extraction (FPSE), 11 matrix solid-phase dispersion (MSPD), 15,22 LLE-solid-phase extraction (LLE-SPE), 16,24,25 QuEChERS extraction, 18 SPE, 21 and subcritical water extraction (SWE). 23 The LLE method for extracting samples is simple, but it consumes a large quantity of reagents and takes a long time and is thus not suitable for batch processing of samples.…”
Section: Selection Of Extraction Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For further evaluation, a comparison of the proposed method with the reported methods in literatures for determining PCM or CAP in animal‐origin foods with SPE is provided in Supporting Information Table S1 and S2. It can be seen that the targets were all extracted with organic solvents.…”
Section: Resultsmentioning
confidence: 99%